Analysis of Diesel Engine Components Durability on Fishing Vessel Fueled with Biodiesel (B30) - Edy Purwanto; Beny Cahyono; Priyonggo Syamrahmadi; Achmad Faisol (Institut Teknologi Sepuluh Nopember, 2021)
The Indonesian government's policy of using biodiesel as an alternative fuel in the shipping industry is still an intensive discussion. Biodiesel as a substitute for diesel fuel has an impact on engine performance, lifetime and emission. The use of biodiesel fuel will increase the wear rate on metal components in diesel engines. From a series of tests carried out in accordance with Engine Manufacturer Association (EMA) standards, wearing on several engine components would be increase when the engine run using biodiesel palm oil (B30). The results showed that there was 19.8% aluminum content, 0.75% iron content, and chromium content in diesel engine lubricating oil with B30 biodiesel fuel higher than using diesel fuel. In addition, the clerance in the pisthon ring also increases and wear is seen on the journal bearing. However, the deposits formation in the diesel engine components made from palm oil biodiesel B30 is 5.43% increase than diesel fuel. From these results, it may be concluded that using of B30 palm oil biodiesel as fuel reduce durability of diesel engine standart.